A low-cost pure water decomposition hydrogen and oxygen production photocatalyst and its preparation method

By using the molten salt method in the photocatalyst and supporting PtNix@CrOy and CoOOH cocatalysts, the existing photocatalyst energy conversion efficiency and precious metal cost are solved, and an efficient and low-cost photocatalytic water decomposition reaction is achieved.

CN119186594BActive Publication Date: 2025-04-25扬州市常发新能源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411572633.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-04-25
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Existing photocatalysts are difficult to reach an economically feasible 5-10% in solar-to-hydrogen (STH) energy conversion efficiency, and the high cost of precious metal cocatalysts limits large-scale commercial applications.

Method used

High crystalline SrTiO3 was prepared as the substrate by molten salt method, and PtNix@CrOy and CoOOH were supported as a cocatalyst. The PtNix@CrOy/SrTiO3/CoOOH nanocomposite photocatalyst was formed by irradiating ultraviolet light source and reacting in ultrapure water.

Benefits of technology

It has achieved high-efficiency photocatalytic reaction under ultraviolet-visible light, with superior photocatalytic activity and high photocatalytic efficiency, and has a significantly reduced cost, which is suitable for large-scale commercial development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186594B_ABST
    Figure CN119186594B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of photocatalytic nanomaterials, and specifically proposes a low-cost pure water decomposition hydrogen and oxygen production photocatalyst and a preparation method thereof. The present invention provides a high-efficiency photocatalytic nanomaterial SrTiO 3 , and loaded with PtNi x @CrO y as a hydrogen evolution promoter, CoOOH as an oxygen evolution promoter, PtNi x Different PtNi with promoter loading of 0.5wt%-5wt% x @CrO y / SrTiO 3 / CoOOH composite nano photocatalytic material. The catalyst of the present invention can realize photocatalytic reaction under ultraviolet-visible light, and can realize decomposition of pure water under visible light in the reaction of photocatalytic decomposition of water, and has excellent photocatalytic activity and high photocatalytic efficiency in the photocatalytic reaction; and the preparation process of the present invention is simple to operate, the experimental environment is safe, the reaction conditions are mild, the technical cost is low, the reagents used are relatively cheap, and it has scalability to meet the possible market demand growth in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalyst nanomaterials, and in particular to a method for preparing a low-cost pure water decomposition photocatalyst for producing hydrogen and oxygen. Background Art

[0002] Energy is the material basis for human survival and development. As one of the most abundant clean and renewable energy sources, the development and utilization of solar energy has received widespread attention worldwide. Hydrogen energy is a clean, zero-carbon, flexible, efficient, and abundant secondary energy source. As an important part of the modern energy system, it is an important carrier for achieving my country's "dual carbon" goals. With the increasingly severe situation of carbon emission reduction, green hydrogen energy has received high attention from the world. Therefore, the use of solar light to decompose water to produce hydrogen technology can achieve green and carbon-free hydrogen energy The entire industry chain, solve the problem of renewable energy consumption, and is a highly promising hydrogen energy development route. In recent years, the conversion of solar energy into clean, zero-carbon hydrogen energy has been widely studied, and some important progress has been made in the field of photocatalytic water splitting in semiconductor powder systems. For example, Domen's team converted 1m of a previously reported Rh@CrOx / Al-SrTiO3 / CoOOH composite photocatalyst into a hydrogen energy source. 2 The flat-plate reactor system was scaled up and a 100m 2 Large-scale photocatalytic solar hydrogen production system. Although the energy conversion efficiency is only 0.76% under natural light, the solar-to-hydrogen (STH) energy conversion efficiency needs to reach 5-10% to achieve economically feasible solar hydrogen production. But this research has opened the prelude to industrialization and successfully achieved commercial operation. However, the price of hydrogen evolution promoter Rh@CrOx is extremely expensive, making it difficult to achieve large-scale commercial hydrogen production applications.

[0003] When the catalytic activity of the HER material is set as a function of the HM (metal) bond strength, it is found that the relationship between the HM bond strength and the HER catalytic activity is in a volcano-like form. This behavior is related to the Sabatier principle, a general explanatory paradigm in heterogeneous catalysis and electrocatalysis, which is used to understand the special activity of precious metals and design metal alloy catalysts. In the specific case of hydrogen evolution, it can be quantified by analyzing the free energy of hydrogen adsorption ΔGH. The free energy of hydrogen adsorption can accurately quantify and predict the HER activity of a variety of metals and alloys, and the optimal ΔGH value should be around 0eV. In the "volcano diagram", the precious metal platinum has the closest adsorption free energy of hydrogen to 0eV, that is, Pt has the best hydrogen adsorption / desorption ability. However, Pt is expensive and has limited reserves. The use of platinum can be reduced to save costs through the platinum-non-precious metal alloy system. This system has extremely low overpotential and extremely high hydrogen evolution efficiency. Nowadays, the interface engineering research on platinum alloys has become an important means to improve the efficiency of nanocatalysis. For example, Huang Yu's group at the University of California used surface modification to prepare a platinum-nickel bimetallic catalyst with nickel hydroxide surface enrichment and nickel hydroxide / platinum {111} heterogeneous interface, achieving the highest value of alkaline electrocatalytic hydrogen evolution mass activity and excellent stability. This move reduces the cost of catalyst raw materials by reducing the amount of platinum, providing a reference for the future industrial production of hydrogen energy.

[0004] So far, the development of noble metal-based co-catalysts has become a frontier scientific issue for improving the performance of photocatalytic water splitting. Bimetallic nanoparticles further enhance the light absorption capacity of composite photocatalysts, and the energy band hybridization between the two metals and the charge redistribution within the bimetallic improve the charge separation efficiency. At the same time, bimetallic nanoparticles provide abundant catalytic active sites for surface reactions to regulate the adsorption and activation behavior of reactants and target products on the catalyst surface, thereby improving the activity and selectivity of photocatalytic reactions. For example, the Amal group prepared alloyed Au-Pt nanoparticle co-catalysts to improve the photocatalytic activity, forming a certain height of Schottky barrier between semiconductor photocatalysts and Au-Pt nanoparticles to promote interfacial charge migration. Therefore, exploring appropriate strategies to construct the optimal height of Schottky barrier and spontaneous electron transfer on semiconductor systems to improve the photoexcited charge separation of catalysts and achieve efficient photocatalytic performance is a scientific issue that needs to be solved urgently. Summary of the invention

[0005] In view of this, the present invention proposes a low-cost pure water decomposition hydrogen and oxygen production photocatalyst and a preparation method thereof.

[0006] The technical solution of the present invention is achieved as follows: The present invention provides a low-cost pure water decomposition hydrogen and oxygen production photocatalyst, the photocatalyst is SrTiO3 prepared by molten salt method as a substrate, and supports PtNi x @CrOy and CoOOH as co-catalysts.

[0007] In some embodiments, the PtNi x The loading amount is 0.5wt%-5wt%, CrO y The loading amount is 0.5wt%-5wt%, and the atomic ratio of Pt to Ni is 1:(0.2-5).

[0008] In some embodiments, the loading amount of CoOOH is 0.5 wt%-5 wt%.

[0009] In some embodiments, the PtNi x Into alloy state.

[0010] In a second aspect, the present invention also provides a method for preparing the above-mentioned low-cost pure water decomposition hydrogen and oxygen production photocatalyst, comprising the following steps:

[0011] (1) uniformly mixing the potassium-containing compound and SrTiO3 nanoparticles by ball milling for 1-24 hours to obtain a first mixture, wherein the atomic ratio of K atoms in the potassium-containing compound to Ti atoms in SrTiO3 is (0.01-0.1):1;

[0012] (2) uniformly stirring the first mixture obtained by ball milling in step (1) with excess SrCl2, and then heat-preserving at 800-1500°C for 4-12 hours to obtain a second mixture, wherein the mass ratio of SrCl2 to SrTiO3 is (15-20):1;

[0013] (3) washing the second mixture after high temperature heat treatment in step (2) to remove excess SrCl2, and drying to obtain highly crystalline SrTiO3 nanoparticles;

[0014] (4) taking a certain amount of SrTiO3 nanoparticles obtained in step (3) and dispersing them in ultrapure water, adding H2PtCl6 solution with a concentration of 0.01-0.05mmol / L and NiCl2 solution with a concentration of 0.01-0.1mmol / L and 20wt% excess methanol, and reacting them under ultraviolet light for 1-10 hours to generate PtNi with a loading of 0.5wt%-5wt% on its surface. x Nanoparticles;

[0015] (5) The PtNi obtained in step (4) x The SrTiO3 / SrTiO3 composite material is added to a 0.01-0.05 mmol / L Cr salt solution and reacted under ultraviolet light for 1-10 hours to generate 0.5 wt%-5 wt% CrO on its surface. y Nanoparticles, washed and filtered to obtain PtNi x@CrO y / SrTiO3 nanocomposite photocatalyst material;

[0016] (6) The PtNi obtained in step (5) x @CrO y The / SrTiO3 composite material is added to a Co salt solution with a concentration of 0.005-0.025mmol / L, and reacted under ultraviolet light for 1-10 hours to generate CoOOH nanoparticles with a loading of 0.5wt%-5wt% on its surface. Finally, PtNi is obtained after washing, filtering and drying. x @CrO y / SrTiO3 / CoOOH nanocomposite photocatalyst materials.

[0017] In the above preparation method, methanol is used as a sacrificial agent (electron donor) to effectively suppress the hole recombination phenomenon by providing electrons to fill holes. This process increases the electron supply in the reaction system, allowing Pt and Ni ions to deposit on the surface of SrTiO3 to form PtNi x Nanoparticles, theoretically the amount of methanol required depends on the number of electrons required in the reaction process, which is related to the number of electrons required for the reduction of Pt and Ni ions. The total number of electrons required is (4*nPt)+(2*nNi), so the number of moles of methanol is [(4*nPt)+(2*nNi)] / 6, and the mass of methanol is 1.2*32.04*[(4*nPt)+(2*nNi)] / 6.

[0018] In some embodiments, the potassium-containing compound is one or more of potassium oxide, potassium carbonate, potassium acetate, potassium nitrate, and potassium chloride.

[0019] In some embodiments, the average particle size of the SrTiO3 nanoparticles in step (3) is 200-500 nm.

[0020] In some embodiments, the PtNi in step (4) x The nanoparticles are alloyed by in situ selective photodeposition.

[0021] In some embodiments, the Cr salt in step (5) is one or more of chromium nitrate, chromium chloride, and chromium acetate.

[0022] In some embodiments, the Co salt in step (6) is one or more of cobalt nitrate, cobalt chloride, cobalt sulfate, and cobalt acetate.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention provides a PtNi x @CrO y / SrTiO3 / CoOOH nanocomposite photocatalyst and preparation method thereof, wherein the photocatalyst is high-crystalline SrTiO3 prepared by molten salt method and loaded with PtNi x @CrO y PtNi is a hydrogen evolution catalyst, and CoOOH is an oxygen evolution catalyst. Compared with the SrTiO3 material prepared by the traditional method, it has higher crystallinity and more stable structure. x @CrO y Hydrogen evolution co-catalyst and previously reported Rh@CrO x Compared with hydrogen evolution co-catalysts, in addition to having efficient photocatalytic activity, the cost is also greatly reduced, which is more conducive to large-scale commercial development and has practical significance. The catalyst of the present invention can realize photocatalytic reaction under ultraviolet-visible light, and can realize the decomposition of pure water under visible light in the photocatalytic water decomposition reaction, and has excellent photocatalytic activity and high photocatalytic efficiency in the photocatalytic reaction; and the preparation process of the present invention is simple to operate, the experimental environment is safe, the reaction conditions are mild, the technical cost is low, the reagents used are relatively cheap, and it has scalability to meet the possible market demand growth in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 The PtNi prepared in Example 1 of the present invention x @CrO y Transmission electron microscopy image of / SrTiO3 / CoOOH nanocomposite photocatalyst;

[0027] Figure 2 PtNi prepared in Example 2 of the present invention x @CrO y High-resolution transmission electron microscopy analysis of / SrTiO3 / CoOOH nanocomposite photocatalyst;

[0028] Figure 3 The photocatalytic water decomposition activity diagram of the nanocomposite photocatalyst prepared in the examples of the present invention and the comparative examples. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0031] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0032] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0033] Example 1

[0034] This embodiment provides a PtNi x @CrO y The preparation method of / SrTiO3 / CoOOH nanocomposite photocatalyst, the preparation steps are as follows:

[0035] Weigh 0.036 mol of strontium titanate and 0.0011 mol of potassium carbonate respectively, mix and grind them in an agate mortar for 1 hour, place the ground mixture in a ball mill, ball mill at 4000 speed for 24 hours, and then add 0.5 mol of strontium chloride and continue ball milling for 1 hour. The ball-milled mixture is sieved and separated, and placed in a muffle furnace and kept warm at 1150 degrees for 10 hours. After taking it out, filter and wash it with a large amount of deionized water, and then place the material in a drying oven at 60°C overnight to obtain SrTiO3 nanoparticles. Then disperse the SrTiO3 nanoparticles in ultrapure water, add 0.02M H2PtCl6 solution and 0.02M NiCl2 solution and an excess of 20wt% methanol, react under ultraviolet light for 1 hour, and generate a PtNi loading of 0.5wt% on its surface. x SrTiO3 nanoparticles were added with 0.05M chromium nitrate aqueous solution and reacted under ultraviolet light for 1 hour to generate 0.5wt% CrO on the surface. y SrTiO3 nanoparticles were washed and filtered, and then 0.05M cobalt nitrate aqueous solution was added in the same way, and the reaction was carried out under ultraviolet light for 1 hour to generate SrTiO3 nanoparticles with a loading of 0.5wt% CoOOH on the surface. Finally, PtNi was obtained after washing, filtering and drying. x @CrO y / SrTiO3 / CoOOH nanocomposite photocatalyst materials.

[0036] The PtNi prepared by the above method x @CrO y / SrTiO3 / CoOOH transmission electron microscopy image Figure 1 As shown, the SrTiO3 nanoparticle size is 200-500 nm, PtNi x @CrO y The co-catalyst nanoparticles and CoOOH co-catalyst nanoparticles are evenly dispersed on the surface of SrTiO3 nanoparticles. It can be observed that the co-catalyst prepared by photodeposition is directional loaded on the corresponding crystal surface of SrTiO3. x @CrO y It is a hydrogen evolution promoter, supported on the (1 0 0) crystal plane, and CoOOH is an oxygen evolution promoter, supported on the (1 1 0) crystal plane.

[0037] Example 2

[0038] This embodiment provides a PtNi x @CrO y The preparation method of / SrTiO3 / CoOOH nanocomposite photocatalyst, the preparation steps are as follows:

[0039] Weigh 0.036 mol of strontium titanate and 0.0011 mol of potassium carbonate respectively, mix and grind them in an agate mortar for 1 hour, place the ground mixture in a ball mill, ball mill at 4000 speed for 24 hours, and then add 0.5 mol of strontium chloride and continue ball milling for 1 hour. The ball-milled mixture is sieved and separated, and placed in a muffle furnace and kept warm at 1000 degrees for 8 hours. After taking it out, it is filtered and washed with a large amount of deionized water, and then the material is placed in a drying oven at 80°C overnight to obtain SrTiO3 nanocatalyst material. After SrTiO3 is evenly dispersed in pure water, 0.02M H2PtCl6 solution and 0.02M NiCl2 solution and an excess of 20wt% methanol are added, and the reaction is carried out under ultraviolet light for 5 hours to generate a 2wt% PtNi on its surface. x The nanoparticles were then dispersed in ultrapure water, and a 0.05M chromium chloride aqueous solution was added. The reaction was carried out under ultraviolet light for 5 hours to generate a 2wt% CrO y SrTiO3 nanoparticles were washed and filtered, and then 0.05M cobalt chloride aqueous solution was added in the same way, and the reaction was carried out under ultraviolet light for 5 hours to generate SrTiO3 nanoparticles with a loading of 2wt% CoOOH on the surface. Finally, PtNi was obtained after washing, filtering and drying. x @CrO y / SrTiO3 / CoOOH nanocomposite photocatalyst materials.

[0040] The PtNi prepared by the above method x @CrO y High-resolution transmission electron microscopy analysis of / SrTiO3 / CoOOH is shown in Figure 2 As shown, by comparing the PDF card, it can be seen that the lattice fringes of the catalyst promoter are 0.213 nm, which is between 0.2265 nm of Pt (111) and 0.2034 nm of Ni (111), proving that it is a Pt-Ni alloy.

[0041] Example 3

[0042] This embodiment provides a PtNi x @CrO y The preparation method of / SrTiO3 / CoOOH nanocomposite photocatalyst, the preparation steps are as follows:

[0043] Weigh 0.036 mol of strontium titanate and 0.0011 mol of potassium carbonate respectively, mix and grind them in an agate mortar for 1 hour, place the ground mixture in a ball mill, ball mill at 4000 speed for 24 hours, and then add 0.5 mol of strontium chloride and continue ball milling for 1 hour. The ball-milled mixture is sieved and separated, and placed in a muffle furnace and kept warm at 1000 degrees for 8 hours. After taking it out, it is filtered and washed with a large amount of deionized water, and then the material is placed in a drying oven at 80 degrees to dry overnight to obtain SrTiO3 nanocatalyst material. After SrTiO3 is evenly dispersed in pure water, 0.02M H2PtCl6 solution and 0.02M NiCl2 solution and an excess of 20wt% methanol are added, and the reaction is carried out under ultraviolet light for 10 hours to generate a PtNi with a loading of 5wt% on its surface. x SrTiO3 nanoparticles. Then PtNi x / SrTiO3 nanoparticles were dispersed in ultrapure water, 0.05M chromium nitrate aqueous solution was added, and the reaction was carried out under ultraviolet light for 10 hours to generate 5wt% CrO on its surface. y The nanoparticles were washed and filtered, and then a 0.05M aqueous solution of cobalt nitrate was added in the same way, and the reaction was carried out under ultraviolet light for 10 hours to generate CoOOH nanoparticles with a loading of 5 wt% on the surface. Finally, the nanoparticles were washed and filtered, and dried to obtain PtNi x @CrO y / SrTiO3 / CoOOH nanocomposite photocatalyst materials.

[0044] Comparative Example 1

[0045] Weigh 0.036mol of strontium titanate and 0.0011mol of potassium carbonate respectively, mix and grind in an agate mortar for 1h, place the ground mixture in a ball mill, ball mill at 4000 speed for 24h, and then add 0.5mol of strontium chloride to continue ball milling for 1h. The ball-milled mixture is sieved and separated, and placed in a muffle furnace and kept warm at 1000 degrees for 8 hours. After taking it out, it is filtered and washed with a large amount of deionized water, and then the material is placed in a drying oven at 80 degrees overnight to obtain SrTiO3 nanocatalyst material. After SrTiO3 is evenly dispersed in pure water, 0.02M H2PtCl6 solution and excess 20wt% methanol are added, and the reaction is carried out under ultraviolet light for 10 hours to generate SrTiO3 nanoparticles with a loading of 5wt% Pt on its surface. Then, Pt / SrTiO3 nanoparticles were dispersed in ultrapure water, and 0.05M chromium nitrate aqueous solution was added. The mixture was reacted under ultraviolet light for 10 hours to generate 5wt% CrO on its surface. yThe nanoparticles were washed and filtered, and then 0.05M cobalt nitrate aqueous solution was added in the same way, and the reaction was carried out under ultraviolet light for 10 hours to generate CoOOH nanoparticles with a loading of 5wt% on the surface. Finally, Pt@CrO y / SrTiO3 / CoOOH nanocomposite photocatalyst materials.

[0046] Comparative Example 2

[0047] Weigh 0.036mol of strontium titanate and 0.0011mol of potassium carbonate respectively, mix and grind in an agate mortar for 1h, place the ground mixture in a ball mill, ball mill at 4000 speed for 24h, and then add 0.5mol of strontium chloride and continue ball milling for 1h. The ball-milled mixture is sieved and separated, and placed in a muffle furnace and kept warm at 1000 degrees for 8 hours. After taking out, filter and wash with a large amount of deionized water, and then place the material in a drying oven at 80 degrees to dry overnight to obtain SrTiO3 nanocatalyst material. After SrTiO3 is evenly dispersed in pure water, add 0.02M NiCl2 solution and excess 20wt% methanol, react under ultraviolet light for 10 hours, and generate SrTiO3 nanoparticles with a loading of 5wt% Ni on its surface. The Ni / SrTiO3 nanoparticles were then dispersed in ultrapure water, and a 0.05 M chromium nitrate aqueous solution was added. The mixture was reacted under ultraviolet light for 10 hours to generate 5 wt% CrO on the surface. y The nanoparticles were washed and filtered, and then 0.05M cobalt nitrate aqueous solution was added in the same way, and the reaction was carried out under ultraviolet light for 10 hours to generate CoOOH nanoparticles with a loading of 5wt% on the surface. Finally, Ni@CrO y / SrTiO3 / CoOOH nanocomposite photocatalyst materials.

[0048] The PtNi prepared in the above examples 1-3 were respectively x @CrO y / SrTiO3 / CoOOH nanocomposite photocatalyst materials and the photocatalysts prepared in Comparative Examples 1 and 2 were subjected to pure water photocatalytic tests and the hydrogen elution rates were statistically analyzed. x / SrTiO3 / CoOOH nanocomposite photocatalyst was used as a reference. Figure 3 As shown, I, II and III represent the samples of Example 3, Example 2 and Example 1, respectively, and the Pt3Ni@CrO x / K, Al-SrTiO3 / CoOOH nanocomposite photocatalysts have a hydrogen evolution rate of 1385 μmol / h / g and an oxygen evolution rate of 659 μmol / h / g, and the photocatalytic performance is higher than that of Rh@CrO x / K, Al-SrTiO3 / CoOOH nanocomposite photocatalysts, and the hydrogen-oxygen ratio is close to 2:1.

[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A low-cost pure water decomposition hydrogen and oxygen production photocatalyst, characterized in that: The photocatalyst is SrTiO3 prepared by molten salt method as a substrate, and supports PtNi x @CrO y and CoOOH as co-catalysts, the PtNi x The loading amount is 0.5wt%-5wt%, CrO y The loading amount is 0.5wt%-5wt%, the atomic ratio of Pt to Ni is 1:(0.2-5), and the preparation method of the low-cost pure water decomposition hydrogen and oxygen production photocatalyst comprises the following steps: (1) uniformly mixing the potassium-containing compound and the SrTiO3 nanoparticles by ball milling for 1-24 hours to obtain a first mixture, wherein the atomic ratio of K atoms in the potassium-containing compound to Ti atoms in SrTiO3 is (0.01-0.1):1; (2) The first mixture obtained by ball milling in step (1) is uniformly stirred with excess SrCl2, and then kept at 800-1500°C for 4-12 hours to obtain a second mixture, wherein the mass ratio of SrCl2 to SrTiO3 is (15-20):1; (3) washing the second mixture after high temperature heat treatment in step (2) to remove excess SrCl2, and drying to obtain highly crystalline SrTiO3 nanoparticles; (4) A certain amount of SrTiO3 nanoparticles obtained in step (3) is dispersed in deionized water, and a 0.01-0.05 mol / L H2PtCl6 solution and a 0.01-0.1 mol / L NiCl2 solution and 20 wt% excess methanol are added. The mixture is reacted under ultraviolet light for 1-10 hours to generate a PtNi with a loading of 0.5 wt%-5 wt% on the surface of the SrTiO3 nanoparticles. x Nanoparticles; (5) The PtNi obtained in step (4) x The SrTiO3 / SrTiO3 composite material was added into a 0.01-0.05 mol / L Cr salt solution and reacted for 1-10 hours under ultraviolet light to generate 0.5wt%-5wt% CrO on the surface of SrTiO3 nanoparticles. y Nanoparticles, washed and filtered to obtain PtNi x @CrO y / SrTiO3 nanocomposite photocatalyst material; (6) The PtNi obtained in step (5) x @CrO y The / SrTiO3 composite material was added to a 0.05 mol / L Co salt solution and reacted under ultraviolet light for 1-10 hours to generate CoOOH nanoparticles with a loading of 0.5 wt%-5 wt% on its surface. Finally, PtNi was obtained after washing, filtration and drying. x @CrO y / SrTiO3 / CoOOH nanocomposite photocatalyst materials.

2. The low-cost pure water decomposition hydrogen and oxygen production photocatalyst as claimed in claim 1, characterized in that: The PtNi x Into alloy state.

3. The low-cost pure water decomposition hydrogen and oxygen production photocatalyst as claimed in claim 1, characterized in that: The potassium-containing compound is one or more of potassium oxide, potassium carbonate, potassium acetate, potassium nitrate and potassium chloride.

4. The low-cost pure water decomposition hydrogen and oxygen production photocatalyst as claimed in claim 1, characterized in that: The average particle size of the SrTiO3 nanoparticles in step (3) is 200-500nm.

5. The low-cost pure water decomposition hydrogen and oxygen production photocatalyst as claimed in claim 1, characterized in that: In step (4), PtNi x The nanoparticles are alloyed by in situ selective photodeposition.

6. The low-cost pure water decomposition hydrogen and oxygen production photocatalyst as claimed in claim 1, characterized in that: In step (5), the Cr salt is one or more of chromium nitrate, chromium chloride and chromium acetate.

7. The low-cost pure water decomposition hydrogen and oxygen production photocatalyst as claimed in claim 1, characterized in that: In step (6), the Co salt is one or more of cobalt nitrate, cobalt chloride, cobalt sulfate and cobalt acetate.

Citation Information

Patent Citations

  • External 36-face {110} crystal face K ion doped SrTiO3 nano photocatalyst and preparation method thereof

    CN114192163A

  • Pt-Ni composite material, preparation method thereof and application of Pt-Ni composite material as water electrolysis hydrogen production catalyst

    CN114457365A